Massively Slipped Vertebral Apophyseal Ring with Intervertebral Disc Herniation in an Overweight Girl: A case report - Prommahachai, Akom (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: To present a rare spine condition in a very young teenage diagnosed combined slipped vertebral apophyseal ring with lumbar disc herniation of L4-5. Methods: The author demonstrates a case by describing the patient’s history, physical examination, imaging, surgical treatment and postoperative outcomes. Literature reviews and discussion were included. Results: An 11-year-old overweight female patient presented with chronic bilateral lumbar radicular pain and neurogenic claudication for 4 months. CT scan of lumbar spine demonstrated a large apophyseal fracture of the inferior end-plate of the L4 vertebral body and MRI showed a massively herniated nucleus pulposus at L4-L5 level. Extensive L4 laminectomy combined with avulsed fragment removal and discectomy was performed to decompress the spinal canal and neural structures. The patient showed a complete absence of the clinical symptoms of radicular pain and claudication within 1 month and regained complete neurological recovery in 3 months. The patient was able to return to full activities of daily living and sport in 6 months after the surgery. Conclusion: Combined slipped vertebral apophyseal ring with lumbar herniated nucleus pulposus in a very young overweight girl is a very rare condition. High degree of suspicion is important to properly investigate these conditions. Adequately surgical decompression is the key to obtain an excellent clinical result.